The 12th Century Milanese Aristocracy Inner Divisions: the Political Causes of the Marginalisation of a capitanei de Raude Branch, Moving from a 1137 Document (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The history of Milan between 1128 and 1145 shows deep changes in the configuration of city’s political space; these changes led to the formation of the consular government. however, this period was an age of deep discord in the city’s society. The political struggle was focused in the contrast between two partes; the struggle between these two local groups overlapped the conflict between Conrad of Swabia and Lothair of Supplinburg for the imperial crown (1125-1135). This conflict had consequences on the family structures of the Milanese élites. Indeed, a document dated to 1137 shows the strong contrasts and divisions that the political struggles had on one of the most important families of the Milanese aristocracy: the capitanei de Raude.
Keywords: Milan; First half of 12th century; political struggle; family discords; aristocracy